Novel neo-clerodane diterpenoids from Teucrium quadrifarium and their anti-ferroptosis effect - Huan Wang; Han-Fei Liu; Xiao-Qiao Yang; Yu-Qiong Liao; Fen-Cong Pan; Jin-Yu Li; Hua-Yong Lou; Wei-Dong Pan (Natural Products and Bioprospecting)
Abstract Teucrifarides A–D (1–4), four previously unreported neo-clerodane-type diterpenoids, combined with sixteen known analogs (5–20), were purified from Teucrium quadrifarium. The absolute forma of compounds 1–4 were determined via spectroscopic and ECD calculation methods, together with X-ray crystallography experiments. Among them, compound 1 possessed a 5,20-epoxy ring featuring a unique cage-like 12-oxatricyclo [5.3.2.01,6]undecane skeleton. Meanwhile, 2 incorporated a 6,20-epoxy ring with a novel 12-oxatricyclo [6.2.2.02,7]undecane skeleton. Compounds 1 and 12 exhibited significant inhibitory effects against HT-22 cells ferroptosis induced by RSL3, with EC50 values of 11.8 ± 1.0 μM, and 4.52 ± 1.24 μM, respectively. Moreover, ROS accumulation in HT22 cells treated with compound 1 was also observed. Graphical Abstract